PROJECT COST ANALYSIS THROUGH EARNED VALUE METHOD ON THE INSTALLATION OF BAGGAGE HANDLING SYSTEM (BHS) PPUPG (PROJECT CASE STUDY AT SULTAN HASANUDIN INTERNATIONAL AIRPORT MAKASSAR) - Pratama, Irwansyah Digma; Nugroho, Laksono Djoko; Muhammadun, Haris (Pusat Publikasi Nusantara, 2025)
This research is aimed at analyzing the cost performance of the Ppupg Baggage Handling System (BHS) Installation project at Sultan Hasanudin Makassar International Airport. This research focuses on two key questions: (1) how to assess cost performance during monitoring using indicators such as Cost Variance and Cost Performance Index, and (2) what the estimated total project cost will be upon completion, specifically through the Estimated All Completion (EAC). The research is conducted from October Week 2 to the field in January 2025 which began in stages from research preparation, initial survey, literature review, data collection, proposal preparation, data analysis, and thesis preparation. The research was conducted in the form of observations, namely, the PPUPG baggage handling system installation project. The study was conducted using a multidisciplinary approach. The analysis of the EAC serves to enhance understanding of projected total project costs, allowing for better financial forecasting and budget management. The findings from this study can help practitioners optimize budgeting processes and improve project outcomes, thereby advancing the overall understanding of cost management in infrastructure projects. Future research can contribute to more effective cost management strategies and improved project performance outcomes by integrating findings from both CPM analysis and comprehensive literature.